Book review: T. V. Paul (Ed.), The China–India Rivalry in the Globalization Era. (June 2019) - Bhalla, Madhu
T. V. Paul (Ed.), The China–India Rivalry in the Globalization Era . New Delhi: Orient BlackSwan, 2019, ₹1195, pp. 351. ISBN: 978-93-5287-520-7.